Memorial de formação: um olhar retrospectivo com reflexões sobre vida e docência - SOUZA, Márcia Andréa Santana de (2020)
This Memorial of Formation aims to describe retrospectively events lived by a life transformed by education: My life. As the author of these writings, I share experiences throughout my family life, while I count my process of academic, academic and professional formation. These are experiences that, under the eyes of today, I was able to resize, considering all the internalized formation in this walk. I show the construction of scientific knowledge in the academy and how these knowledges led me to reflect on teaching practices in the perspective of their changes, in particular, the Youth and Adult Education (EJA). A life trajectory that runs through the suffering caused by bullying, and other memories, in the midst of these processes of formation and development as a person and teacher. I show the understanding of theories that help my thinking about a praxis in education as a teacher who is finally formed to resume this praxis. I report beliefs and values and their contributions in the conquest of the greatest professional dream: teaching. In a moment of reflection and re-signification of ethics, love and respect, I was able to understand the value of experience as a knowing in a movement to be touched and transformed by lived events. Events that led me to search for answers specifically in my own self and made me reflect on my role as a change agent in education. Finally, all the experiences reported in this memorial - with reflections on painful, challenging, happy and rewarding moments - have given me a movement of re-signification of the way of being, being, thinking and acting in the world for the sake of education. At the end of it, I can say that I have won and that I will finally be a teacher and then continue my teaching career.